Identifying the system of value factors of green consumer choice - Liudmyla Potrashkova; Viktor Zaruba; Diana Raiko; Oleksiy Yevsyeyev (Innovative Marketing, 2024)
To justify the production of green products, it is necessary to anticipate the choice of consumers toward products with different environmental friendliness. Therefore, it is necessary to understand the factors that determine this choice, particularly value factors. The study is based on the idea that a consumer is stimulated to eco-consumption by a set of values, not excluding individualist values; and the influence of values is mediated by motives. The purpose of the study is to develop the theoretical foundations of constructing a three-level system of value factors of green consumption on the example of office paper consumption. As a result, the study formed a system of factors containing preferences, motives, and values of office paper consumers. According to the proposed approach, for each respondent, quantitative characteristics of the elements of the system of factors were determined through a survey, which made it possible to identify correlation relationships between the elements. A pilot study was used to test the proposed approach to constructing a value factors system. The results of the pilot survey showed a positive connection between eco-friendliness of consumer preferences – through motives – with such values as “Nature,” “Self-development,” “Country success,” and “Social power.” This finding provides additional justification for the assumption that individuals are driven to green consumption not only by socially oriented values but also by individualistic values. Identifying the value factors of green consumption will allow predicting consumer behavior and influencing it through targeted marketing offers.